Growth Performance of Apical and Nodal Cuttings of Selected Forest Tree Species Under Different Fertilizers and Substrate Regimes in the Nursery - Kamara, Ernest Gibril; Kamara, Patricia; Mattia, Stephen B.; Kassoh, Fayia A; Kanu, Sheku Alfred (European Journal of Applied Sciences, 2025)
The main aim of clonal propagation program is the production of high-quality timber and faster tree growth. An experiment was established from wood shoot cuttings of 3-year-old hedged Acacia and Eucalyptus stock plants grown in a hedge garden at Miro Mile 91, in northern Sierra Leone to study the effects of branch position, fertilizer application and substrate on growth of seedlings. A completely randomized design in factorial arrangement was used for experimentation. Coppice shoots collected from the apical and nodal leafy cuttings were prepared. These cuttings were planted in root trainers using soil and cocopeat as growth media and cultured in a mist chamber for rooting at 85 ± 2% relative humidity with maximum and minimum day-night temperature at 32 ± 18C and 26 ± 18C respectively. The results showed that the rooting parameters viz., percent rooting, mean number of leaves sprout, shoot length, and mean number of roots and length per cutting were signiﬁcantly inﬂuenced by the branch position, substrate, and fertilizer treatments. Treatments with apical cuttings treated with 20g/L and 30g/L NPK fertilizer increased percent rooting and percent sprouting compared to those treated with 10g/L NPK and the control. Cocopeat substrate had significantly higher aeration and water holding porosity than sterilized soil. The results indicated that Apical cuttings treated with 20g/L or 30g/L NPK fertilizer using cocopeat medium could be used for successful clonal propagation of Eucalyptus and Acacia species. Apical cuttings, cocopeat substrate and NPK fertilizer are recommended for mass clonal propagation of these two species.